"Gawe kuta baluwarti bata kalawan kawis"; Contribution of local knowledge to the expansion of the Banten Sultanate on the Nusantara spice route - Rismawidiawati, Rismawidiawati; Handoko, Wuri; Tabroni, Roni; Hamid, Abd. Rahman; Subair, Muh. (Wacana, Journal of the Humanities of Indonesia, 2023)
So far, the trade and spice route historiography has focused on social, political, and economic aspects. This discussion is also fragmentarily or is part of another focus. No studies have discussed the relationship between local knowledge practices, spice routes, power networks, and Islamization. However, the spice trade and Islamization are two intersecting events important for their connection with the local culture. This article assumes that there was a local knowledge used as a strategy by the Banten rulers as a response to trade, Islamization, and power networks in the sixteenth and seventeenth centuries. It finds that Sultan Maulana Yusuf’s policy, known as “gawe kuta baluwarti bata kalawan kawis”, was a local knowledge that continued to be used by Banten rulers throughout the sixteenth-seventeenth centuries. This local knowledge was transformed from its literal meaning of “building cities and fortresses from bricks and corals” into a metaphor representing development that considered the duality of Banten’s potential. This local knowledge became the foundation stone for the strategies of Banten’s rulers until Sultan Ageng Tirtayasa to respond the challenges posed by the trade, power network, and Islamization. This application of the local knowledge carried the Banten Sultanate to its peak of advancement during the reign of Sultan Ageng Tirtayasa (1651-1682). In his sponsorship of this local knowledge, the ruler of the Banten appears as a technocrat, trader, scholar, leader, and ruler who paved the way for the expansion of the Banten Sultanate. This local knowledge was passed down from generation to generation and remains the local knowledge of the Banten people today. This study reconstructs the historiography of the existing spice route by according local knowledge (gawe kuta baluwarti bata kalawan kawis), the leading role in shaping the expansion of the Banten Sultanate in the century of the spice trade and the extension of the spice route.